International Evidenceon the Determinants of Private Saving - Masson, Paul (IMF Working Papers; Working Paper ;, 1995)
A broad set of possible determinants of private saving behavior is examined, using data for a large sample of industrial and developing countries. Both time-series and cross-section estimates are obtained. Results suggest that there is a partial offset on private saving of changes in public saving and (for developing countries) in foreign saving, that demographics and growth are important determinants of private saving rates, and that interest rates and terms of trade have positive, but less robust, effects. Increases in per capita GDP seem to increase saving at low income levels (relative to the United States) but decrease it at higher ones.